Determination of steroid hormones in sediments based on quick, easy, cheap, effective, rugged, and safe (modified-QuEChERS) extraction followed by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Issue 22 (22nd October 2015) - Camilleri, Julien; Vulliet, Emmanuelle
Abstract : The method enables the determination of the target analytes with limits of detection comprised between 0.03 and 0.2 ng g ¬1 and limits of quantification comprised between 0.1 and 0.6 ng g ¬1 . Abstract : Hormones, constantly excreted by humans and animals, are discharged into surface waters via various routes including municipal and industrial sewage treatment plants and also animal agriculture and aquaculture. Many analytical methods have been studied, developed and used for the determination of hormones in the aqueous phase while the study of the particulate phase (suspended solids, sediment, and soil) was less developed due to more complex pre-treatment. This paper describes a simple, rapid and effective procedure based on modified-QuEChERS to analyze targeted hormones with very different chemical structures, from river sediments. We coupled this sample preparation method with LC-MS/MS for the detection and quantification, the whole method proposed is both selective and sensitive. Except for the more hydrophobic compound, the recoveries are higher than 74%. The repeatability is comprised between 2 and 36% and the intermediate precision is comprised between 4 and 30%, depending on the compound and the level. The method enables the determination of the target analytes with limits of detection comprised between 0.03 and 0.2 ng g −1 and limits of quantification comprised between 0.1 and 0.6 ng g −1 . It is applied to the analysis of sediments collected at four points of the Bourbre river (Isère, France) and its tributary in October 2011. The results reveal the presence of estrone (up to >40 ng g −1 ) and tamoxifen in all the samples (≥0.6 ng g −1 ).